A Day Late and A Dollar Short? A Study of Budget Passage in New York State. (7th July 2016) - Yi Lu, Elaine; Chen, Gang
Abstract : Passing a budget is an attribute of sovereignty. This research highlights the fusion of multiple forces in the broader context—economic factors, political factors, budget rules, and leadership stability—in which budget negotiation takes place. Through an in‐depth case study of New York State from 1970 to 2012 and extensive interviews with prior and current key participants in the budgeting process, this research found that a divided government contributes to a late budget only when budget rules are not controlled. In addition, legal clarity of authorities among the key budget negotiators, their willingness to compromise, as well as effective executive leadership in bringing people to budget negotiation, hold the potential to reduce the extent of budget delays in an increasingly contentious and turbulent budgeting environment.